2019
DOI: 10.1111/phor.12300
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral outcrop models for palaeoseismic studies

Abstract: The traditional study of palaeoseismic trenches, involving logging, stratigraphic and structural interpretation, can be time consuming and affected by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…It has been shown that LiDAR-derived terrain information can be used to correct geometric distortions in the hyperspectral data [27,28], and also to enhance geological interpretation [29,30,31]. Similarly, Salehi (2018), and Kirsch ( , 2019 [32,33,34,35] proposed workflows that integrate spectral products with 3D photogrammetric terrain data, demonstrating the advantages of terrestrial hyperspectral sensing for mapping vertical geological outcrops in extreme regions not observable by air or spaceborne sensors. Ghamisi (2018) [36] surveyed and analysed other classification techniques, such as those based on mathematical morphology, Markov random fields, tree partitioning and sparse representation.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that LiDAR-derived terrain information can be used to correct geometric distortions in the hyperspectral data [27,28], and also to enhance geological interpretation [29,30,31]. Similarly, Salehi (2018), and Kirsch ( , 2019 [32,33,34,35] proposed workflows that integrate spectral products with 3D photogrammetric terrain data, demonstrating the advantages of terrestrial hyperspectral sensing for mapping vertical geological outcrops in extreme regions not observable by air or spaceborne sensors. Ghamisi (2018) [36] surveyed and analysed other classification techniques, such as those based on mathematical morphology, Markov random fields, tree partitioning and sparse representation.…”
Section: Related Workmentioning
confidence: 99%
“…The area has a rich mining history dating back to the Bronze Age, while currently, significant resources remain and mining operations still take place. Panoramic outcrop scans were acquired by an AISA-FENIX camera, mounted on a tripod [34]. The captured HSI is composed of 300 × 1416 pixels and 190 spectral bands, covering the range between 0.38 and 2.50 µm.…”
Section: The Geological Spain Datasetmentioning
confidence: 99%
“…In this case study, the following surface coverages were achieved per sensor: The used UAS-fitted workflows are matured to a high user friendliness and could be flexibly adapted to all mining and exploration scenarios, where high resolution and spatial coverage is required. Safety concerns for detailed mapping along pit walls are mitigated by UAS mapping, when used for vertical outcrop scanning along unstable wall sections [67].…”
Section: Assessing the General Uas Survey Workflow With Focus On Imagmentioning
confidence: 99%